2023
DOI: 10.1093/molbev/msad018
|View full text |Cite
|
Sign up to set email alerts
|

A Single Nucleotide Variant in the PPARγ-homolog Eip75B Affects Fecundity in Drosophila

Abstract: Single nucleotide polymorphisms are the most common type of genetic variation, but how these variants contribute to the adaptation of complex phenotypes is largely unknown. Experimental evolution and genome-wide association studies have demonstrated that variation in the PPARγ-homolog Eip75B is associated with longevity and life-history differences in the fruit fly Drosophila melanogaster. Using RNAi knockdown, we first demonstrate that reduced expression of Eip75B in adult flies affects lifespan, egg-laying r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“… 22 Now, we are able to generate, study, and compare human neuronal cells with only a single nucleotide difference across the entire genome, as we and others have previously reported. 21 , 30 , 67 , 68 , 69 , 70 , 71 This approach provides the opportunity to elucidate the individual contributions of risk variants in a human- and disease-relevant system. Here, we apply this strategy to study a GWAS-identified, non-coding variant implicated in SCZ risk, rs4129585.…”
Section: Discussionmentioning
confidence: 99%
“… 22 Now, we are able to generate, study, and compare human neuronal cells with only a single nucleotide difference across the entire genome, as we and others have previously reported. 21 , 30 , 67 , 68 , 69 , 70 , 71 This approach provides the opportunity to elucidate the individual contributions of risk variants in a human- and disease-relevant system. Here, we apply this strategy to study a GWAS-identified, non-coding variant implicated in SCZ risk, rs4129585.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular modeling is quickly becoming a powerful tool for the study of genetic risk variants, particularly those within non-coding regions of the genome, as technological advances are being made in genome editing, iPSC generation from somatic cells, and directed differentiation methods 22 . Now, we are able to generate, study, and compare human neuronal cells with only a single nucleotide difference across the entire genome, as we and others have previously reported 21,29,[66][67][68][69][70] . This approach provides the opportunity to elucidate the individual contributions of risk variants in a human-and disease-relevant system.…”
Section: Discussionmentioning
confidence: 99%
“…Mifepristone was recently reported to inhibit an estrogen-related receptor ( ERR ) transgenic reporter in adult Drosophila, and to reduce lipid staining and magro RNA levels in the midgut in flies of undefined sex [ 46 ], and in the future it may be of interest to test loss of function of Drosophila ERR for ability to mimic the benefits of mifepristone. Finally, naturally-occurring genetic variation in the Drosophila gene Eip75B has been found to be associated with adult life span and fecundity [ 47 , 48 ], and experimental knock-down studies in adult flies show that Eip75B is required for midgut hypertrophy in response to mating [ 11 , 12 , 15 ], for normal adult life span and egg production [ 48 , 49 ], and for normal sugar tolerance and expression of de novo lipogenesis genes [ 50 ]; in the future it may be of interest to determine if adult-specific knock-down of Eip75B might affect the response to mifepristone.…”
Section: Discussionmentioning
confidence: 99%